Microscopia de força atômica aplicada em imunoensaios - Ferreira, Antonio Aparecido Pupim [UNESP]; Yamanaka, Hideko [UNESP] (Sociedade Brasileira de Química, 2006)
Affinity reactions have been used for specific detection of their complementary partners and an enormous variety of enzyme-linked immunosorbent assay (ELISA) formats are used in research and in routine serological tests. With the advent of the atomic force microscopy (AFM) technique, the immune reactions have been monitored by these devices. In the present article we focus on applications of AFM to immunoassays. After introducing the basic concepts of AFM, a brief discussion on the monitoring of the interactions between antigens and antibodies through both topographic image and biosensor systems is presented.
Atomic force microscopy applied to immunoassays
Keywords: atomic force microscopy; antigen-antibody; immunoassay